The Effect of Sustainability Disclosure on Firm Value Moderated by Good Corporate Governance - Laksmana, Chelsy Velinda; Hartono, Wendra (Journal of Management Studies and Development, 2025)
The importance of sustainability disclosures has gained increasing attention in recent years, particularly among stakeholders aiming to maximize wealth by increasing firm value. This research aims to examine the moderating role of good corporate governance on the effect of economic, environmental, and social disclosure on firm value. This study adopted a quantitative approach with an associative design, using content analysis with the GRI 2021 Standards.  The research focused on companies listed on the SRI KEHATI index from 2019 to 2023. The results indicate that only economic disclosure has a significant effect on firm value. Board size is not relatively effective in moderating the effect of economic, environmental and social disclosure on firm value. Audit committee meetings only can moderate the effect of economic disclosure on firm value. The presence of independent commissioners can effectively moderate the effect of economic, environmental, and social disclosures on firm value. Firms may leverage the findings of this research to evaluate the implementation of sustainability reporting. At the same time, investors are encouraged to focus on both financial and sustainability disclosures when making investment decisions.